(3aGVMI GdedMOjf hfGUMI GdehMOjfs - (3YdGA GdOjf GdHNGQj , eMeO Hf eMeO Hf eMeO GdHNGQj, YdGA GdOjf,J (B841 (3g` s ((3eMeO Hf YKeGf GdOejGWj s)
(3ChdgG (B:s
(3hHYO aEf Gddg fhQ HQMeJg Ndb GdYHGO hHjf dge SHd GdQTGO hYfO Pdc jfJgj JUQa GdYbd s
(3BNQgG (B:s
(3hjHYO eG JbOe ef GdCdaGX hGddg SHMGfg hJYGdi CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B294s
Keywords: (3GdJhMjO hGdedd hGdfMds